RBTT-04. DOES EXERCISE IMPROVE PROGRESSION FREE SURVIVAL AND QUALITY OF LIFE IN PATIENTS WITH GLIOBLASTOMA? A TRIAL IN PROGRESS. (5th November 2018) - Edelstein, Kim; Campbell, Kristin; Bernstein, Lori; Lax, Ilyse; Backhouse, Felicity; Pond, Gregory; Kalidindi, Navya; Or, Rosemarylin; Laperriere, Normand; Millar, Barbara-Ann; Shultz, David; Berlin, Alejandro; et al.
Abstract: BACKGROUND: Glioblastoma is the most common adult malignant glioma, with poor prognosis and adverse neurological sequelae. Physical activity improves outcomes in patients with other cancers, but has not been evaluated in GBM. This prospective, single-arm intervention trial examines feasibility and preliminary efficacy of exercise on progression-free survival (PFS), cognition and quality of life (QOL) in newly diagnosed GBM patients. METHOD: Participants are English-speaking GBM patients scheduled for concurrent chemo-radiation at the Princess Margaret Cancer Centre, 18–65 years old, ECOG 2. The 3-month home-based exercise program, prescribed by a physiotherapist, includes aerobic and resistance training, tailored to prior fitness level, current physical status, and individual interests. Assessments of physical and neurocognitive functions, mood, fatigue, sleep, and QOL, occur within 2 weeks of starting chemo-radiation, and approximately 3, 6, 12, and 18 months later, or until tumor progression. Feasibility will be assessed by accrual, retention, and adherence rates. Outcomes include PFS (RANO criteria), change in cognition, physical activity and sleep (actigraphy, self-report questionnaires). Time-to-event outcomes will be estimated (Kaplan-Meier), and mixed modelling will explore individual and disease variables that contribute to outcomes. RESULTS: During the first seven months of recruitment, 51 newly diagnosed GBM patients scheduled to be treated at our institution were screened, 25 met eligibility criteria, and 16 consented. Four participants did not complete the exercise program; 3 withdrew consent, 1 refused concurrent chemoradiation. Two participants died after the intervention and one other progressed. No exercise-related serious adverse events occurred. Updated accrual and feasibility details will be presented at the meeting. DISCUSSION: Exercise appears feasible for GBM patients. Preliminary efficacy in terms of survival, performance status, cognition, sleep, mood, and QOL are under study. Results may guide physical activity recommendations in GBM, lay the groundwork for a larger randomized controlled trial, and generate avenues for translational research.